2013
DOI: 10.1186/1475-2840-12-173
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of plasma cholesterol and lipoprotein parameters are related to a higher degree of insulin sensitivity in high HDL-C healthy normal weight subjects

Abstract: BackgroundWe have searched if plasma high density lipoprotein-cholesterol (HDL-C) concentration interferes simultaneously with whole-body cholesterol metabolism and insulin sensitivity in normal weight healthy adult subjects.MethodsWe have measured the activities of several plasma components that are critically influenced by insulin and that control lipoprotein metabolism in subjects with low and high HDL-C concentrations. These parameters included cholesteryl ester transfer protein (CETP), phospholipid transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The most important antiatherogenic function of HDL is reverse cholesterol transport [120]. HDL also exhibits other potential cardioprotective functions such as anti-oxidative, anti-inflammatory and endothelium-dependent vasodilatory effects [121][122][123].…”
Section: Tg and Hdlmentioning
confidence: 99%
“…The most important antiatherogenic function of HDL is reverse cholesterol transport [120]. HDL also exhibits other potential cardioprotective functions such as anti-oxidative, anti-inflammatory and endothelium-dependent vasodilatory effects [121][122][123].…”
Section: Tg and Hdlmentioning
confidence: 99%
“…In this regard LCAT activity is higher in individuals with low HDL-C plasma concentration and the CETP activity does not differ between individuals with low and high plasma HDL-C levels [14]. VLDL transports less than 20% of NCSPCS.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, HDL particle size and volume were significantly lower, indicating a possible increase in HDL catabolism. Previous findings from our group in another cohort of healthy, normal weight individuals, demonstrated that plasma HDL-C variations are related to several parameters controlling plasma lipoprotein metabolism and to the degree of insulin sensitivity (Leanca et al, 2013). In fact, the isolated low HDL-C is commonly found with hyperinsulinism, without hypertriglyceridemia or other lipoprotein variations (Rashid et al, 2003;Karhapaa et al, 1994).…”
Section: Discussionmentioning
confidence: 93%